2020
DOI: 10.2147/cmar.s249678
|View full text |Cite
|
Sign up to set email alerts
|

<p>A Trial of the Safety and Efficacy of Chemotherapy Plus Anlotinib vs Chemotherapy Alone as Second- or Third-Line Salvage Treatment for Advanced Non-Small Cell Lung Cancer</p>

Abstract: Purpose: Anlotinib is a newly developed oral multitarget tyrosine kinase inhibitor. We retrospectively evaluated the toxicity and clinical efficacy of chemotherapy combined with anlotinib versus chemotherapy alone for metastatic/advanced non-small cell lung cancer (NSCLC) in patients who failed firstor second-line systemic treatment in China. Patients and Methods: In this retrospective trial, ninety-four advanced NSCLC patients received chemotherapy combined with anlotinib (n = 41) or chemotherapy alone (n = 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…Three studies were excluded because they presented single-center data from the ALTER 0303 study [ 27 – 29 ]. Two studies were excluded because they were retrospective studies [ 30 , 31 ]. All studies were conducted in China.…”
Section: Resultsmentioning
confidence: 99%
“…Three studies were excluded because they presented single-center data from the ALTER 0303 study [ 27 – 29 ]. Two studies were excluded because they were retrospective studies [ 30 , 31 ]. All studies were conducted in China.…”
Section: Resultsmentioning
confidence: 99%
“…The ALTER 0303 study and previous real-world studies showed that anlotinib alone could improve prognosis in NSCLC patients as third or later line treatment. Furthermore, the combination of anlotinib with immunotherapy, target therapy, or chemotherapy has been shown to have synergetic efficacy (22)(23)(24)27). We retrospectively analyzed real-world data to determine the efficacies of these therapeutic strategies in NSCLC, paying special attention to the combination of anlotinib plus immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“… 30 , 31 In addition, anlotinib has been shown to have synergistic effects with chemotherapy and targeted therapies. 32 , 33 Adverse effects of anlotinib monotherapy have been shown to be manageable in previous studies. 34–36 Based on the ALTER0303 study, anlotinib has been approved as an NSCLC standard third-line treatment indication.…”
Section: Discussionmentioning
confidence: 99%